Suppression of lusitropy as a disease mechanism in cardiomyopathies - Marston, Steven; Pinto, Jose Renato (Frontiers in Cardiovascular Medicine, 2023)
In cardiac muscle the action of adrenaline on β1 receptors of heart muscle cells is essential to adjust cardiac output to the body’s needs. Adrenergic activation leads to enhanced contractility (inotropy), faster heart rate (chronotropy) and faster relaxation (lusitropy), mainly through activation of protein kinase A (PKA). Efficient enhancement of heart output under stress requires all of these responses to work together. Lusitropy is essential for shortening the heartbeat when heart rate increases. It therefore follows that, if the lusitropic response is not present, heart function under stress will be compromised. Current literature suggests that lusitropy is primarily achieved due to PKA phosphorylation of troponin I (TnI) and phospholamban (PLB). It has been well documented that PKA-induced phosphorylation of TnI releases Ca2+ from troponin C faster and increases the rate of cardiac muscle relaxation, while phosphorylation of PLB increases SERCA activity, speeding up Ca2+ removal from the cytoplasm. In this review we consider the current scientific evidences for the connection between suppression of lusitropy and cardiac dysfunction in the context of mutations in phospholamban and thin filament proteins that are associated with cardiomyopathies. We will discuss what advances have been made into understanding the physiological mechanism of lusitropy due to TnI and PLB phosphorylation and its suppression by mutations and we will evaluate the evidence whether lack of lusitropy is sufficient to cause cardiomyopathy, and under what circumstances, and consider the range of pathologies associated with loss of lusitropy. Finally, we will discuss whether suppressed lusitropy due to mutations in thin filament proteins can be therapeutically restored.